Risk Regulation and Critical Infrastructure Protection: The New Winds of the Regulatory Phenomenon - Guterres, Egon C. (Law, State and Telecommunications Review, 2016)
Purpose ”“ This article analyzes the origins of the Risk Regulation Theory and Critical Infrastructure Protection Programs, and shows their contribution to the Brazilian regulatory experience. Methodology/approach/design ”“ Through several examples, this study presents regulatory policies that emerged as responses to events that caused a significant impact on society. Findings ”“ The unique way that the Critical Infrastructure Protection Programs evolved within the Brazilian regulatory experience is greatly attributable to demands of major international sporting events.